Poverty, gender and life-cycle under the English poor law, 1760-1834 - Williams, Samantha, 1970- (Boydell & Brewer, 2011)
Social welfare, increasingly extensive during the seventeenth and eighteenth centuries, was by the first third of the nineteenth under considerable, and growing, pressure, during a "crisis" period when levels of poverty soared. This book examines the poor and their families during these final decades of the old Poor Law. It takes as a case study the lived experience of poor families in two Bedfordshire communities, Campton and Shefford, and contrasts it with the perspectives of other participants in parish politics, from the magistracy to the vestry, and from overseers to village rat.
Keywords: Public welfare -- England -- History -- 19th century.; Poor laws -- England -- History -- 19th century.; Poverty -- England -- History -- 19th century.; Poor -- England -- History -- 19th century.; Poor -- England -- Bedfordshire -- History -- 19th century -- Case studies.; Aide sociale -- Angleterre -- Histoire -- 19e siècle.; Pauvreté -- Angleterre -- Histoire -- 19e siècle.; Pauvres -- Angleterre -- Histoire -- 19e siècle.; Pauvres -- Angleterre -- Bedfordshire -- Histoire -- 19e siècle -- Études de cas.; Lois sur les pauvres -- Angleterre -- Histoire -- 19e siècle.; SOCIAL SCIENCE -- Poverty & Homelessness.; HISTORY -- Modern -- General.; Poor; Poor laws; Poverty; Public welfare; England; England -- Bedfordshire; 1800-1899; Electronic books.; Case studies; History